2021
DOI: 10.1136/bmjopen-2020-048198
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported impact of myasthenia gravis in the real world: protocol for a digital observational study (MyRealWorld MG)

Abstract: IntroductionMyasthenia gravis (MG) is a rare, chronic, autoimmune disease, mediated by immunoglobulin G antibodies, which causes debilitating muscle weakness. As with most rare diseases, there is little patient-reported data with which to understand and address patient needs. This study explores the impact of MG in the real world from the patient perspective.Methods and analysisThis is a 2-year prospective, observational, digital, longitudinal study of adults with MG, resident in the following countries: the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…MG is a rare disease, with an estimated 60,000 cases of MG in the United States (US) [ 7 , 8 ]. As with many rare diseases, because of the relatively low prevalence compared with more common diseases, there is a lack of real-world studies in MG to understand and address patients’ unmet needs and the burden of disease [ 9 ]. While randomized clinical trials are necessary to obtain robust efficacy and safety data on a treatment, observational real-world studies are also important as they can provide information on larger, more representative populations compared with clinical trials, and an understanding of the true progression and management of the disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…MG is a rare disease, with an estimated 60,000 cases of MG in the United States (US) [ 7 , 8 ]. As with many rare diseases, because of the relatively low prevalence compared with more common diseases, there is a lack of real-world studies in MG to understand and address patients’ unmet needs and the burden of disease [ 9 ]. While randomized clinical trials are necessary to obtain robust efficacy and safety data on a treatment, observational real-world studies are also important as they can provide information on larger, more representative populations compared with clinical trials, and an understanding of the true progression and management of the disease [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…As with many rare diseases, because of the relatively low prevalence compared with more common diseases, there is a lack of real-world studies in MG to understand and address patients’ unmet needs and the burden of disease [ 9 ]. While randomized clinical trials are necessary to obtain robust efficacy and safety data on a treatment, observational real-world studies are also important as they can provide information on larger, more representative populations compared with clinical trials, and an understanding of the true progression and management of the disease [ 9 ]. An analysis of insurance claims between 2010 and 2019 from the IBM® MarketScan® database showed that 91% of patients living with MG in the US received drug therapy, and 40% of those received non-steroidal immunosuppressive treatment (IST) or biologics [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, they have provided input into the publication and communication plan of the study and are offered the opportunity to coauthor resulting academic papers. 9 …”
Section: Methodsmentioning
confidence: 99%
“…In recent years, interest has been growing in the emotional, socio-familial, and humanistic aspects of MG, as well as the effects of medical interventions on disease burden [ 6 , 7 , 8 , 9 , 10 ]. This scenario is especially crucial for patients with treatment-refractory MG [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%